Socio-Economic Transformation Through Digital Agriculture Platforms in Dehradun and Haridwar (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Dehradun and Haridwar are two famous cities in the Indian state of Uttarakhand, and this research looks at the social and economic changes that have occurred there as a result of digital agriculture platforms. As a result of digital platforms, farmers are seeing increased production, better access to markets, and more opportunity to make money as a result of the technological revolution in agriculture. Mobile apps, online markets, and data-driven services are some of the digital technologies that this article looks at, and how they've affected farmers' socioeconomic situations. This study uses a mixed-methods strategy to examine the pros and cons of these platforms by surveying and interviewing local farmers. By improving information availability and decreasing market inefficiencies, digital agriculture has greatly enhanced economic results, according to the research. A number of obstacles, including a lack of technical knowledge, inadequate infrastructure, and limited resources, persist, nonetheless. In order to encourage sustainable agricultural growth in these areas and increase digital adoption, the research finishes with policy suggestions.